Social Entrepreneurship in Remote Communities: Pathways to Sustainable Economic Empowerment - Imam Jayanto; Ilyas Ilyas; Merita Ayu Indrianti; Bernardus Agus Rukiyanto (Pengabdian: Jurnal Abdimas, 2026)
Social entrepreneurship has gained increasing attention as a development approach capable of addressing persistent economic challenges in remote communities where market access, infrastructure, and state support remain limited. Geographic isolation and structural vulnerability often restrict livelihood opportunities, making conventional development strategies less effective. This study aims to analyze how social entrepreneurship functions as a pathway to sustainable economic empowerment in remote communities by integrating economic activities with social objectives and community participation. The research employs a qualitative design grounded in development studies, combining in-depth interviews, participant observation, and document analysis of community-based social enterprises operating in remote areas. The findings show that social entrepreneurship contributes to sustainable economic empowerment through income diversification, skill development, and the strengthening of social capital. Social enterprises foster local agency, collective ownership, and resilience, enabling communities to adapt to economic uncertainty while reducing dependency on external assistance. Empowerment outcomes extend beyond financial gains to include enhanced participation, trust, and institutional capacity at the community level. The study concludes that social entrepreneurship represents a socially embedded and context-sensitive development strategy that supports long-term economic empowerment in remote communities. Effective support for social enterprises requires policies and interventions that prioritize participation, local knowledge, and sustainability rather than standardized entrepreneurial models.